Applying Haptic Systems in Serious Games: A Game for Adult’s Oral Hygiene Education - Rodrigues, Herbet Ferreira; Machado, Liliane S.; Valença, Ana Maria Gondim (Journal on Interactive Systems, 2014)
Most commonly used in virtual reality systems, haptic devices are taken as an important way of providing greater interaction and engagement between the user and the computer system, particularly in problems that depend on skill and use the sense of touch. It is known that the development of serious games, composed by immersive environments and unconventional devices can contribute with the motivation and learning of the players. However, an important question relates to how to integrate these devices to conform its limitations to a specific problem addressed in serious game. In the present work it is presented a study related to the integration of haptic systems for serious games for adult oral hygiene in order to adjust teaching content to computational resources. Thus, a specific process model to the development of serious games was applied to the creation of TouchBrush serious game, dedicated to education of good tooth brushing practices.